ENT 300 Dreamland Travel Agency / Leonard Imban Sodusta... [et.al] - Sodusta, Leonard Imban; Bilong, Augustine Seli; Gunong, Jenny; Berawi, Khadtizah Khamsyiah; Jugah, Shirly; Sajali, Norfaizah (2006)
Our company is known as DREAMLAND TRAVEL AGENCY. The business is in the form of partnership, which consists of six members. Each partner contributes certain amounts of cash as agreed in our agreement. Our main business activity is selling services towards the tourist which is come from within and outside our country Malaysia. Our business will be operating at lot 82, n83, section 50 KTLD at Jin Abell, 93450, Kuching, Sarawak. All partners are entitled to participate in the business management. We have agreed that Leonard Imban Sodusta is the General Manager, Augustine Seli Bilong is the Administration Manager,Jenny Gunong is the Marketing Manager, Khadtizah Khamsyiah is the Operational Manager, Shirty Jugah is the Financial Manager and Norfaizah Sajali as finance assistant. The management will be lead by General Manager and assisted by other managers. The General Manager is responsible in controlling, leading, organizing, and planning the entire business. Administration Manager is responsible for the entire jobs related to office administration. The Marketing manager is responsible in preparing marketing plan. This includes identifying the target market share, develop sales forecast and develop the marketing strategies. The operation of our business is controlled and monitored by Operation Manager. All workers who work in our company are working under operation manager